Pengaruh Etos Kerja, Motivasi dan Disiplin terhadap Kinerja Guru SMP Negeri di Kabupaten Pidie Jaya - Fachrurazi, Fachrurazi; Azhari, Azhari (Aceh Cooperative Care, 2022)
ABSTRACT: This study aims to explore further and provide empirical information about the effect of work ethic, motivation and teacher discipline on the performance of state junior high school teachers in Pidie Jaya Regency. This research is in the form of a survey with a questionnaire instrument, and uses quantitative and associative descriptive methods between variables with analytical tools with a path analysis model approach. The results found: 1) There is a direct and indirect effect of work ethic on teacher performance by 41.92%, 2) There is a direct and indirect effect of motivation on teacher performance by 32.07%, 3) There is a direct and indirect effect of discipline teachers on the performance of Pidie Jaya Junior High School teachers, namely 58.31%. And 4) Simultaneously work ethic, motivation and discipline have a positive effect on the performance of Pidie Jaya State Junior High School teachers with the contribution of these three factors amounting to 42.30%